Herbal medicines as a sustainable strategy in the treatment of generalized anxiety symptoms (Research, Society and Development, 2023)
Medicinal plants continue to be a rich source of biomolecules with therapeutic values ​​for the treatment of anxiety and depression, thus, the study seeks to categorize the species recognized as medicinal plants based on two clinical symptoms of two anxiety disorders. Objectively, they are categorized as species recognized as medicinal plants based on two clinical symptoms and two anxiety disorders, disclosing the uses, types and families with phytotherapeutic applications. This is an literature review study, the databases selected for Science direct, VHL Regional Portal, PubMed.gov and Springer Link. using the described: (Medicinal plants) AND (Anxiety) AND (Symptoms) AND (Public Health) AND (Biodiversity). Foram found in a universe of 163 species. As foram species categorized, the type of action found considering the criteria of the Diagnostic and Statistical Manual of Mental Disorders-V (DSM-V). Symptoms evaluated for nervousness, sleeplessness and agitation. As species that have multiple uses, they can be used in order to reduce various symptoms. In conclusion, these results reinforce the potential use of these species in anxiety therapy.